Parallel-/Reimport, Patenterschöpfung und Recycling in Japan – mit Blick auf das deutsche Schrifttum - Mishiro, Michiyoshi (Zeitschrift für Japanisches Recht, 2007)
The purpose of patent law is not only to protect inventions but also to foster industrial development (Art. 1 Patent Act). Industry forms part of any national economy whose foundation is a free market economy relying on the free movement of goods, persons, services, and capital. The development of a national free market economy is the main aim of competition and economy policies in the free world and thus also in the EU. Patent enforcement should therefore also be in line with these goals. The principle of exhaustion of patents as developed under German law limits the enforcement of a patent independent of the will of the patentee, weighing the interests in protecting the patent against those in guaranteeing the free movement of goods. If products are put on the market in one jurisdiction by the patentee, or with his consent, national patents can no longer be invoked. This is uncontested in the cases mentioned. However, if the products are first put in circulation abroad, the patentee can, according to German prevailing opinion, enforce his patent within the EU or the EEA. In Japan, this issue is disputed. There are attempts to justify the different treatment of products first put in circulation either within one jurisdiction or abroad on the basis of patent law. The author suggests that the arguments are based on considerations quite contrary to the role of patent law proper, i.e. on economic reasons, above all supporting the pricing policy of national enterprises, which should indeed be left to the individual market participants. The protection of the environment is another aspect that may justify the limitation of patent rights. Products which, for economic reasons, are intended only for a short period of usage should be recycled as far as possible. Business activity helps to enhance and advance the environmental protection. Also, there has to be a just differentiation between the areas where patent protection applies and those where environmental protection applies. On the one hand, case law has tried to differentiate between lawful repair and illegal reconstruction. On the other, the principle of patent exhaustion has been developed further. This paper analyzes the different positions taken in German and Japanese writings on international patent exhaustion, while also taking into account the limitations of German sovereignty by EU law. The focus of the paper is on a view consistent with competition. (Translation by the Editors)